Dosimetric Characterisation of Er-doped Optical Fibre as Thermoluminescent Material - Y.A, Abdulla; Y.M, Amin; D.A, Bradley, (Malaysian Journal of Science (MJS), 2002)
ABSTRACT A radiation dosimeter based on Er-doped optical fibre is described. The thermoluminescence characteristics induced by Ã¢ÂÂ¶Ã¢ÂÂ°Co irradiation are investigated.These characteristics including reproducibility, photon dose response, minimum detectable dose, fading and annealing procedure.